(untitled) (Jóvenes en la Ciencia, 2024)
The appearance of contraceptive methods dates back to the late 19th and 20th centuries, with the development of medicine, especially in the field of endocrinology and gynecology. The objective of the research is to determine the incidence of depression in fertile women who are treated with hormonal methods. It is a quantitative, cross-sectional study that will be carried out in forms. The convenience sample size included young women aged 18-29 years who use or have used some type of hormonal contraceptive method. According to the results obtained, there is a percentage of 65.3% of women who affirm that their mental health has not been unstable due to the use of hormonal contraceptives. It is concluded that hormonal contraceptive methods do not affect the emotional state of the women surveyed, despite the fact that they are aware that hormones do affect the mental health of some women.